GERAKAN LITERASI SEKOLAH SMA NEGERI 10 PALEMBANG - Indani, Nur (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The School Literacy Movement strengthens the movement of growth in character as outlined in the Minister of Education and Culture Regulation No. 23 of 2015. One of the activities in the movement is